Views of Patients, Nursing and Technical Staff and Medical Students on Patient Care in Tertiary Level Hospitals - Nikita, Nikita; Nautiyal, Tanisha; Ashraf, Hamim; Rakhiyani, Lavina; Jangid, Amit; Bhatia, Srishti; Sharma, Shivani; Gautam, Mimansha; Kumar Garg, Hemant; Singh, Rukmini (Journal of Neonatal Surgery, 2025)
Background: Patient care in tertiary level hospitals is a multifaceted process influenced by healthcare providers’ attitudes, training, and institutional resources. Understanding the perspectives of medical students, nursing students, and technical staff provides insights into strengths and gaps in patient-centered care. Objectives: To assess and compare the views of medical students, nursing students, and technicians/nursing staff on various domains of patient care, including patient dignity, communication, time spent with patients, availability of resources, and overall satisfaction. Methods: A cross-sectional, questionnaire-based study was conducted among 100 medical students, 50 nursing students, and 100 technicians/nursing staff in a tertiary care hospital. Participants rated five domains of patient care using a 5-point Likert scale. Data were analyzed descriptively and presented using tables and visual charts (bar and pie). Results: Nursing students reported the highest satisfaction across most domains, particularly for patient dignity (4.4) and overall satisfaction (4.3). Medical students expressed moderate satisfaction, with lower ratings for time spent with patients (3.5). Technicians and nursing staff reported relatively lower scores, particularly for communication (3.7) and resource availability (3.8). Comparative analysis revealed that perceptions varied significantly by role, with nursing students being most favorable toward patient care. Conclusion: While overall perceptions of patient care were positive, differences emerged between groups. Nursing students demonstrated the most favorable outlook, reflecting their direct patient engagement and communication-focused training. Medical students showed moderate satisfaction, limited by clinical exposure and workload, whereas technicians and nursing staff highlighted systemic challenges. Recommendations include enhancing communication and empathy training in medical curricula, leadership training for nursing students, workload and resource management for technical staff, and hospital-wide policies promoting patient dignity and interprofessional collaboration.